Cytokine and chemokine multiplex analysis-based exploration for potential treatment and prognostic prediction in large-vessel vasculitis: A preliminary observational study - Abe, Nobuya; Kono, Michihiro; Kono, Michihito; Katsuyama, Takayuki; Ohmura, Kazumasa; Sato, Taiki; Karino, Kohei; Fujieda, Yuichiro; Kato, Masaru; Hasebe, Rie; Murakami, Masaaki; Atsumi, Tatsuya (Frontiers in Immunology, 2022)
Large-vessel vasculitis (LVV) is subclassified into two phenotypes; Takayasu arteritis and giant cell arteritis. Although the pathogenesis of LVV is not fully established, IL-6-IL-17 axis and IL-12-IFN-γ axis play critical roles in the disease development. We aimed to clarify the association between the disease state and cytokine/chemokine levels, to assess disease course as prognosis and to predict regulators in patients with LVV using the blood profiles of multiple cytokines/chemokines. This retrospective analysis comprised 35 LVV patients whose blood were collected, and multiplex cytokine/chemokine analysis with 28 analytes was performed. The differences of cytokines/chemokines corresponding disease status, upstream regulator analysis, pathway analysis and cluster analysis were conducted using the cytokines/chemokines profile. Relapse-free survival rate was calculated with Kaplan-Meier analysis in the classified clusters. In the robust analysis, IL-4, CCL2/MCP-1, TNFSF13/APRIL, TNFSF13B/BAFF, CHI3L1 and VEGF-A levels were significantly changed after treatment. Untreated LVV patients demonstrated activation of NFκB-related molecules and these patients are potentially treated with JAK/STAT inhibitors, anti-TNF-α inhibitors and IL-6 inhibitors. Cluster analysis in active LVV patients revealed two clusters including one with high blood levels of IL-1β, IL-6, IL-17, IL-23 and CCL20/MIP-3. A subgroup of the LVV patients showed activated IL-17 signature with high relapse frequency, and JAK/TyK2 inhibitors and IFN-γ inhibitors were detected as potentially upstream inhibitors. Blood cytokine/chemokine profiles would be useful for prediction of relapse and potentially contributes to establish therapeutic strategy as precision medicine in LVV patients.